Empowering Santri in Managing Emotions through Dhikr Education Based on Islamic Psychology - Nailis Sa’adah; Farid Azfaruddin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Adolescence is a period marked by significant emotional changes, making the ability to regulate emotions particularly important. Santri (Islamic boarding school students) who live in pesantren face various academic, social, and spiritual demands that can lead to emotional pressure. Therefore, appropriate strategies are needed to strengthen santri’s emotional regulation skills. This community service program aimed to enhance santri’s ability to regulate emotions by teaching dhikr using an Islamic psychology approach. The method employed was an educative–participatory approach that actively involved santri as participants. The activities were conducted in several sessions, including psychoeducation on emotional regulation, instruction and guided practice of dhikr, and reflection activities. Data were collected through observation, brief interviews, and questionnaires administered before and after the program. The results showed an increased understanding among santri regarding emotional regulation and the role of dhikr in maintaining emotional stability. In addition, santri demonstrated positive behavioral changes, becoming calmer, more focused, and better able to control their emotions in daily life at the pesantren. These findings indicate that dhikr education based on Islamic psychology is effective in supporting mental health and character development among santri.